Graphene as a piezo-resistive coating to enable strain monitoring in glass fiber composites. (28th July 2021) - Reghat, Mojdeh; Mirabedini, Azadeh; Tan, Adin Ming; Weizman, Yehuda; Middendorf, Peter; Bjekovic, Robert; Hyde, Lachlan; Antiohos, Dennis; Hameed, Nishar; Fuss, Franz Konstantin; Fox, Bronwyn
Abstract: In this study, the electromechanical properties and strain monitoring behavior of graphene-coated glass fiber reinforced epoxy (GGFRE) composites were investigated. Glass fabrics were first coated with 2 wt% graphene dispersions using a blade coating method and composites of these graphene-coated glass fabrics were manufactured using vacuum resin infusion. As-prepared GGFRE showed an increase in normalized resistance (ΔR/R0 ) by 4.46%, 10.5%, 11.07% and 11.27% proportional to the applied cyclic tensile forces up to 2000N, 3000N, 4000N and 5000N, respectively. The corresponding gauge factors were calculated to be 14.56 ± 1, 13.32 ± 1, 11.23 ± 0.5 and 8.69 ± 2, respectively. It was also observed that under cyclic tensile loadings at 2000N, ΔR/R0 values were consistent within 11 cycles indicating a reliable sensing performance. The integration of graphene into the composite has shown to decrease the tensile strength as well as flexural strength and flexural modulus by 26%, 37% and 39%, respectively. This drop is believed to be caused by the lower fiber volume content in the GGFRE compared to that of the neat glass fiber composite and the ineffective interfacial interaction between the glass fiber and the graphene dispersion. The piezo-resistive behavior indicated by GGFRE along with their scalable manufacturing method suggest them as promising potential candidates for strain sensing applications. Graphical abstract: Image 1